Virtual Power Electronics Labs for Online Teaching - Darwish, Mohammed K.; Amreiz, Hassan Musa; Janbey, Alan; Marouchos, Christos (My University, 2020)
A textbook and traditional classroom only approach in teaching power electronics can mean that design of power electronic circuits could be isolated and will be difficult to absorb by students. If we add to this, the sudden switch to virtual delivery of lectures then the challenge to engage the students in the learning process of power electronics could be even more complicated. In this paper, a virtual way of teaching power electronic circuits without much compromise with real practical environment is presented. A boost and flyback converter circuits are presented as a case study where all practical parameters are considered in the 'virtual' practical circuit.
Keywords: Virtual Labs; Online electric teaching labs